Museums and Development of Communities in Rukiga District: A Case Study of Great Lakes Museum. - Tumuheirwe, Judith (Kabale University, 2024)
The study about the development of Communities in Rukiga District was carried out with three main objectives; to find out the contribution of museums to the development of communities in Rukiga District, to find out the challenges faced by museums in Rukiga District, and to find out the possible solutions to the challenges faced by museum industry in Rukiga District. The study used a cross-sectional design while collecting data and this was achieved along with research instruments like questionnaires, interviews, and observations. Qualitative and quantitative research methodologies were used to analyze data collected from the field and to draw recommendations and conclusions. Results revealed that museums are very important to the development of communities by providing education, storage, and preservation, carrying out research, curriculum development, and being agents of change and development in society. The study concluded that natural disasters, environmental changes, being a barrier against modernization and lack of security are the major challenges facing museums. The study concluded that promoting exhibitions, adapting to technology, support packages that combine museum entrance, local transportation, and access to other cultural activities, and using a proactive approach are possible solutions to the challenges facing museums. The study recommended that there is a need to set up more museums in different areas because of their importance in communities especially in Education and research to help students access them easily without paying much money for transport to access them. The government should reduce internet costs to help museums promote their exhibitions internally using technology. Internet costs are high and if not reduced it will remain a nightmare for museums to promote their items locally, nationally, and internationally.